Analisis SWOT Implementasi Program Tahfizh Al-Qur'an Berjenjang untuk Penghafal Al-Qur'an yang Berakhlak Al-Qur'an di SMP Tahfidz Ma'had Tafaqquh, Kampar, Riau. - Abdul Wahid Wandana (Mathematics Education Study Program, 2025)
The background of this study analyzes the implementation of the Tiered Tahfizh Al-Qur'an Program at Ma'had Tafaqquh Al-Islami Junior High School to produce good moral memorizers of the Qur'an. Using SWOT analysis, this study identifies strengths, weaknesses, opportunities, and challenges in program implementation to provide recommendations for improving its effectiveness. The focus of the research includes aspects of the strengths and weaknesses of the program, the opportunities and challenges faced, and the moral values of the Qur'an that are reflected in the memorizers. This study uses a qualitative approach with a descriptive design, collecting data through observation, interviews, and documentation. The research informants consisted of leaders, principals, teachers, and students. The results show that the strength of the program lies in the support of leaders, an effective tiered system, integrated teaching methods, and conducive technology and environmental support. However, there are drawbacks related to limited time, teaching resources, and facilities. Opportunities for program development are identified through the implementation of an effective quarantine system, the quality of teachers, and the support of parents and the community. The main challenges include limited student time and lack of family support. Moral values such as honesty (ash-shidq), patience (as-sabr), responsibility (al-amanah), and social concern (al-ihsan) are reflected in the memorizers, which form their character in social and academic life. In the tahfizh process, students are taught to be honest in their memorization and social life, be patient in facing challenges, be responsible for their memorization, and care and help others in the learning process.